2008
DOI: 10.2215/cjn.01790408
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, Social Support, and Survival in Hemodialysis Patients

Abstract: Background and objectives:No studies have evaluated the relationship among spirituality, social support, and survival in patients with ESRD. This study assessed whether spirituality was an independent predictor of survival in dialysis patients with ESRD after controlling for age, diabetes, albumin, and social support.Design, setting, participants, & measurements: A total of 166 patients who had ESRD and were treated with hemodialysis completed questionnaires on psychosocial variables, quality of life, and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
3
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 42 publications
5
63
3
10
Order By: Relevance
“…Patel et al, 2002;Song and Hanson, 2009); recruiting participants from one dialysis unit (e.g. Ko et al, 2007;Martinez and Custodio, 2014) and studying a non-representative sample of the dialysis population such as African Americans (Spinale et al, 2008;Thomas and Washington, 2011) or women only (Tanyi and Werner, 2008b). One qualitative study in this review (Yodchai et al, 2011) recruited a sample of only five participants and so, based on its findings, it might not be possible to conclude that all patients employ spirituality/religion as a way of coping with their disease.…”
Section: Sample Size and Studied Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…Patel et al, 2002;Song and Hanson, 2009); recruiting participants from one dialysis unit (e.g. Ko et al, 2007;Martinez and Custodio, 2014) and studying a non-representative sample of the dialysis population such as African Americans (Spinale et al, 2008;Thomas and Washington, 2011) or women only (Tanyi and Werner, 2008b). One qualitative study in this review (Yodchai et al, 2011) recruited a sample of only five participants and so, based on its findings, it might not be possible to conclude that all patients employ spirituality/religion as a way of coping with their disease.…”
Section: Sample Size and Studied Populationmentioning
confidence: 99%
“…Only three studies were identified in the review that explore the relationship between spirituality and survival (Spinale et al, 2008), spirituality and satisfaction with care (Berman et al, 2004) and spirituality and treatment preferences (Song and Hansen, 2009) in patients with ESRD. All were conducted in the USA and used cross-sectional design and valid measures to assess spirituality and religion (as shown in Table 3.5).…”
Section: Spirituality and Survival Satisfaction With Care And Treatmmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis seems more likely given that the authors refer to a study showing that the effects of spirituality can already be mediated by better social support alone. 9 Although their study design implies they had the chance, the authors did not acknowledge this and did not collect information on general attitude and social environment to be able to assess whether any additional influence of religiosity did exist.…”
mentioning
confidence: 99%